Evaluating the role of NTHL1 p.Q90* allele in inherited breast cancer predisposition. Issue 11 (19th September 2020) - Kumpula, Timo; Tervasmäki, Anna; Mantere, Tuomo; Koivuluoma, Susanna; Huilaja, Laura; Tasanen, Kaisa; Winqvist, Robert; de Voer, Richarda M.; Pylkäs, Katri
ABSTRACT: Background: Rare protein truncating variants of NTHL1 gene are causative for the recently described, recessively inherited NTHL1 tumor syndrome that is characterized by an increased lifetime risk for colorectal cancer, colorectal polyposis, and breast cancer. Although there is strong evidence for breast cancer being a part of the cancer spectrum in these families, the role of pathogenic NTHL1 variants in breast cancer susceptibility in general population remains unclear. Methods: We tested the prevalence of NTHL1 nonsense variant c.268C>T, p.Q90*, which is the major allele in NTHL1 families and also shows enrichment in the Finnish population, in a total of 1333 breast cancer patients. Genotyping was performed for DNA samples extracted from peripheral blood by using high‐resolution melt analysis. Results: Sixteen NTHL1 p.Q90* heterozygous carriers were identified (1.2%, p = 0.61): 5 in hereditary cohort (n = 234, 2.1%, p = 0.39) and 11 in unselected cohort (n = 1099, 1.0%, p = 0.36). This frequency is equal to that in the general population (19/1324, 1.4%). No NTHL1 p.Q90* homozygotes were identified. Conclusion: Our results indicate that NTHL1 p.Q90* heterozygous carriers do not have an increased risk for breast cancer and that the variant is unlikely to be a significant contributor to breast cancer risk at the population level. Abstract : Although there is strong evidence for breast cancer being a part of the cancer spectrum of recessively inherited NTHL1 tumor syndrome, the role of pathogenic NTHL1 variants in breast cancer susceptibility in the general population remains unclear. Here, we have tested the prevalence of NTHL1 nonsense variant c.268C>T, p.Q90*, which is the major allele in NTHL1 families and also shows enrichment in the Finnish population, in a total of 1333 breast cancer patients. Our results indicate that NTHL1 p.Q90* heterozygous carriers do not have an increased risk for breast cancer and that the variant is unlikely to be a significant contributor to breast cancer risk at the population level, a notion that is particularly important for genetic counseling.